Pengaruh Gaya Hidup Hedonisme Dan Financial Technology Terhadap Pengelolaan Keuangan Dengan Literasi Keungan Sebagai Variabel Intervening Pada Para Ibu Rumah Tangga Di Wilayah Kenjeran Rw.10 Surabaya - Prewati, Puri Handayani Sura; Slamet Riyadi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze the influence of hedonistic lifestyle, financial technology (fintech), and financial literacy on household financial management among housewives in the Kenjeran RW 10 area of Surabaya. The research uses the Structural Equation Modelling (SEM) method with Amos 24 software and primary data collected through a Google Form-based questionnaire. The results of the study show that hedonistic lifestyle and financial literacy have a significant impact on financial management. Financial literacy also significantly affects financial management, with hedonistic lifestyle influencing financial management indirectly through financial literacy as an intervening variable. However, financial technology (fintech) does not show a significant impact on either financial literacy or financial management, both directly and indirectly. This may be due to a lack of education on the use and benefits of fintech among housewives. This research provides insights into the importance of financial literacy in managing household finances and avoiding a hedonistic lifestyle, and suggests the need for further education on fintech.